The global logic of development aid: projects for the landless poor. Issue 1 (2nd January 2020) - Leahy, Terry; Mahmoud, Amira
ABSTRACT: Reformist critics of globalisation see global governance as the solution to poverty relief in the developing world. Marxist critics see this poverty as an effect of global structures. Yet governments and NGOs continue to construct local projects. How do these projects fit a global analysis of power? Most projects seek to integrate the poor. This article asks whether projects might work better by detaching participants from global capitalism. Focusing on the landless poor, the second part of the article examines common strategies for localised interventions in the developing world. Examples come from fieldwork in Egypt and Sub-Saharan Africa.